2015
DOI: 10.1016/j.ygeno.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of GPR126 gene polymorphism with adolescent idiopathic scoliosis in Chinese populations

Abstract: Idiopathic scoliosis is the most common pediatric spinal deformity affecting 1% to 3% of the population, and adolescent idiopathic scoliosis (AIS) accounts for approximately 80% of these cases; however, the etiology and pathogenesis of AIS are still uncertain. The current study aims to identify the relationship between G protein-coupled receptor 126 (GPR126) gene and AIS predisposition, to identify the relationship between the genotypes of the GPR126 SNPs and the clinical phenotypes of AIS. We conducted a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 40 publications
1
36
1
1
Order By: Relevance
“…This finding has been replicated in a small Chinese candidate gene study [62]. A knockdown of GPR126 in zebrafish caused delayed ossification of the developing spine [61].…”
Section: Summary Of Genetic Findings In Idiopathic Scoliosismentioning
confidence: 71%
“…This finding has been replicated in a small Chinese candidate gene study [62]. A knockdown of GPR126 in zebrafish caused delayed ossification of the developing spine [61].…”
Section: Summary Of Genetic Findings In Idiopathic Scoliosismentioning
confidence: 71%
“…Our study was performed in patients who were unrelated, and we found a risk for one marker. Xu et al [20] recently reported a case-control study that genotyped twenty SNPs of the GPR126 gene in unrelated AIS patients. They further added 10 exonic SNPs and 10 intronic polymorphisms in patients and compared them to those in controls, finding strong evidence in 30% of SNPs studied.…”
Section: Discussionmentioning
confidence: 99%
“…rs7774095, an intronic SNP of GPR126 , was first reported to be associated with AIS in a Japanese population in 2013 . Other studies in southern Chinese populations replicated the association of this locus . However, there was no clear functional evidence provided for this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Xu et al . found this locus and two other loci (rs7774095 and rs7755109) in 352 southern Chinese cases and 149 controls. Recently, Qin et al .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation